Structural studies of phosphorylation-dependent interactions between the V2R receptor and arrestin-2 - Qing-Tao He (Nature Portfolio, 2021)
The interaction between a GPCR, such as the vasopressin receptor-2 (V2R), and arrestin depends on the receptors’ phosphorylation pattern. Here authors use FRET and NMR to analyze the phosphorylation patterns of the V2R-arrestin complex and show that phospho-interactions are the key determinants of selective arrestin conformational states and correlated functions.